The Role of Oxygen Therapy in Normoxemic Acute Coronary Syndrome: A Systematic Review of Randomized Controlled Trials. Issue 6 (November 2018) - Hu, Xinyu; Cheng, Shijiao; Yin, Yuehui; Ning, Lin; Xiang, Liquan; Zhou, Yinpin
Abstract : Background: Supplemental oxygen has been commonly used in the cases of acute coronary syndrome (ACS); however, recent evidence suggests that high-concentration oxygen supplementation and hyperbaric oxygen in ACS patients are associated with adverse cardiovascular effects. Objective: The purpose of this article is to systematically review the role of supplemental oxygen therapy in normoxemic patients with ACS. Methods: A search for randomized controlled trials before November 2017 in biomedical databases was performed, and a total of 6 eligible studies with 7508 participants were identified. Four studies reported all-cause mortality after randomization, whereas 3 studies measured myocardial infarct size using cardiac enzyme levels and magnetic resonance imaging. The effect size of our primary end point was the odds ratio for all-cause mortality. The mean difference was calculated as a secondary outcome for myocardial infarct size. Results: Compared with ambient air or titrated oxygen, high-concentration oxygen therapy did not significantly decrease all-cause mortality (odds ratio, 1.01; 95% confidence interval [CI], 0.81–1.25; P = .95) within 1 year nor infarct size detected by peak cardiac troponin (mean difference, −0.53 ng/mL; 95% CI, −1.20 to 0.14; P = .12) and magnetic resonance imaging (mean difference, 1.45 g; 95% CI, −1.82 to 4.73; P = .39). These outcomes were listed through a fixed-effects model because of low statistical heterogeneity across the studies. Conclusions: Oxygen therapy did not significantly reduce clinical all-cause mortality and myocardial infarct size in ACS patients with normoxemia. Further large-scale randomized clinical trials are warranted to evaluate the cardiovascular effects in this field. Abstract : Supplemental digital content is available in the text.